1996
DOI: 10.3109/08820139609059316
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of Susceptibility to Antigen-Induced Arthritis into Severe Combined Immunodeficient (SCID) MICE: Role of CD4+ and CD8+ T Cells

Abstract: Antigen-induced arthritis (AIA) in mice occurs after immunization and a subsequent intra-articular injection with methylated bovine serum albumin (mBSA). The role of T lymphocytes in the adoptive transfer of susceptibility to AIA into SCID mice was investigated. Pooled spleen and lymph node cells from immunized syngeneic or allogeneic donor mice, isolated either before or after the induction of arthritis, could transfer the capacity both to develop arthritis and to produce antibodies to mBSA, collagen type II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 4 publications
1
43
0
Order By: Relevance
“…Because AIA is characterized as a Th1-dependent experimental model of joint disease (43,44), the demonstration of a suppressive IL-10 orientated T cell response in ASC Ϫ/Ϫ mice could be a possible link to the observed reduced inflammatory status in these animals, although we cannot directly correlate this altered T cell phenotype in ASC Ϫ/Ϫ mice with their milder disease outcome. Our results are in agreement with previous studies that have shown that the development of Th1-mediated experimental arthritis is critically linked with the balance of cytokines produced by Th1/ Th2 cells (45)(46)(47).…”
Section: Discussionmentioning
confidence: 72%
“…Because AIA is characterized as a Th1-dependent experimental model of joint disease (43,44), the demonstration of a suppressive IL-10 orientated T cell response in ASC Ϫ/Ϫ mice could be a possible link to the observed reduced inflammatory status in these animals, although we cannot directly correlate this altered T cell phenotype in ASC Ϫ/Ϫ mice with their milder disease outcome. Our results are in agreement with previous studies that have shown that the development of Th1-mediated experimental arthritis is critically linked with the balance of cytokines produced by Th1/ Th2 cells (45)(46)(47).…”
Section: Discussionmentioning
confidence: 72%
“…However, the overwhelming influx of neutrophils, as opposed to T cells, into the joints throughout a 5-day period of AIA is surprising, given the observations that arthritis cannot be induced in nonimmunized mice by i.a. mBSA injection (39) and that susceptibility can be adoptively trasferred by CD4 ϩ T cells from AIA donors to SCID mice (62). One of the possible explanations for the predominance of joint-homing neutrophils in this otherwise T cell-dependent model of arthritis is the presence of immune compexes (ICs).…”
Section: Discussionmentioning
confidence: 99%
“…The AIA model is dependent on CD4ϩ T cells and Th1-type immunity, as well as the presence of mBSA-specific antibodies and mBSA immune complexes in the serum and joint tissues of animals with established disease (19,46). A role for presentation of autoantigen has been hypothesized in AIA based on increased T cell responses to type II collagen and proteoglycan in arthritic animals (47).…”
Section: Discussionmentioning
confidence: 99%